Bio-distribution of pharmacologically administered recombinant factor VIIa (rFVIIa) - Gopalakrishnan, R. (2009)
BACKGROUND: Recent clinical studies suggest that the prophylactic use of recombinant factor VIIa (rFVIIa) markedly reduces the number of bleeding episodes in hemophilic patients with inhibitors. Given the short biological half-life of rFVIIa, it is unclear how rFVIIa could be effective in prophylactic treatment. OBJECTIVES: To examine the extravascular distribution of pharmacologically administered rFVIIa to obtain clues on how rFVIIa could work in prophylaxis. METHODS: Recombinant mouse FVIIa tagged with AF488 fluorophore (AF488-FVIIa) was administered into mice via the tail vein. At different time intervals following the administration, mice were exsanguinated and various tissues were collected. The tissue sections were processed for immunohistochemistry to evaluate distribution of rFVIIa. RESULTS: rFVIIa, immediately following the administration, associated with the endothelium lining of large blood vessels. Within 1 h, rFVIIa bound to endothelial cells was transferred to the perivascular tissue surrounding the blood vessels and thereafter diffused throughout the tissue. In the liver, rFVIIa was localized to sinusoidal capillaries and accumulated in hepatocytes. In bone, rFVIIa was accumulated in the zone of calcified cartilage and some of it was retained there for a week. The common finding of the present study is that rFVIIa in extravascular spaces was mostly localized to regions that contain TF expressing cells. CONCLUSIONS: The present study demonstrates that pharmacologically administered rFVIIa readily associates with the vascular endothelium and subsequently enters into extravascular spaces where it is likely to bind to TF and is retained for extended time periods. This may explain the prolonged pharmacological effect of rFVIIa.